Tunisian-Libyan Foreign Policy After 2011 (Comprehensive Journal of Science, 2026)
Tunisia and Libya remain at a crossroads. Although Libya has opened a new      chapter in its transition must confront the third impossibility: securing the country from the start, unifying it, and paving the way for successful general elections. Thus, Tunisia succeeds in consolidating its democracy in a society experiencing economic, social, and political crises, The Libyan investments in the tourism sector declined by approximately 60 percent following terrorist attacks in 2015 and 2016 involving Tunisian extremists with ties to Libya. The Libyan crisis has negatively impacted the flow of foreign investment and reduced the number of tourists seeking to spend their holidays in Tunisia. According to the Barcelona Centre for International Affairs, approximately three million Tunisians depend on Libya, either through remittances from Tunisian workers or black market activities in the border region. The World Bank estimates that the Libyan crisis was responsible for 24 percent of Tunisia's economic growth slowdown between 2011 and 2015. Since then, this figure has increased significantly, amounting to approximately 2 percent of GDP annually.